2015
DOI: 10.1039/c5ra14637b
|View full text |Cite
|
Sign up to set email alerts
|

Amide functionalized metal–organic frameworks for diastereoselective nitroaldol (Henry) reaction in aqueous medium

Abstract: The two new metal-organic frameworks (MOFs) of zinc(II) and copper(II) [Zn 2 L 2 (1,4-BDC)] n ⋅ ⋅ ⋅ ⋅2n(DMF) (1) and [Cu(L) 2 ] n .4n(DMF).n(H 2 O) (2) (L = 4-(pyridin-4ylcarbamoyl)benzoate; BDC = benzenedicarboxylate), respectively, have been synthesized from a pyridyl amide functionalized benzoic acid (HL). They were characterized by elemental, FT-IR, thermogravimetric, powder X-ray and single crystal X-ray diffraction analyses. Single crystal Xray crystallography reveals that 1 and 2 exhibit 2D and 3D polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 130 publications
3
27
1
Order By: Relevance
“…The results show that the aromatic aldehydes with electron-donating substituents (OCH 3 or CH 3 , Table 3, entries 1-4) exhibit a lower reactivity than those bearing electron-withdrawing groups (NO 2 , Br or Cl, Table 3, entries 7-12) due to the higher electrophilicity of the aldehyde in the latter case. In comparison to the scarce examples found in the literature for the catalytic nitroaldol reaction in water, using catalysts based on different metals (Table S3), the conversions obtained in this work are comparable, or better in some cases, taking into consideration the indicated reaction conditions such as temperature, amount of catalyst, and reaction time [43,44,[60][61][62][75][76][77][78][79][80]. Based on the study of several variables, it was found that the best reaction conditions to obtain the highest possible yield of β-nitro alcohols using catalyst 1 (5 mol%) is by heating the reaction mixture at 100 ºC for 48 h in a mixture of water and MeOH.…”
Section: Catalytic Activitysupporting
confidence: 56%
See 1 more Smart Citation
“…The results show that the aromatic aldehydes with electron-donating substituents (OCH 3 or CH 3 , Table 3, entries 1-4) exhibit a lower reactivity than those bearing electron-withdrawing groups (NO 2 , Br or Cl, Table 3, entries 7-12) due to the higher electrophilicity of the aldehyde in the latter case. In comparison to the scarce examples found in the literature for the catalytic nitroaldol reaction in water, using catalysts based on different metals (Table S3), the conversions obtained in this work are comparable, or better in some cases, taking into consideration the indicated reaction conditions such as temperature, amount of catalyst, and reaction time [43,44,[60][61][62][75][76][77][78][79][80]. Based on the study of several variables, it was found that the best reaction conditions to obtain the highest possible yield of β-nitro alcohols using catalyst 1 (5 mol%) is by heating the reaction mixture at 100 ºC for 48 h in a mixture of water and MeOH.…”
Section: Catalytic Activitysupporting
confidence: 56%
“…Activation of the carbonyl group using Lewis acidic metal compounds for catalytic Henry reaction is an approach that has been intensively studied and performed with (i) a well-defined complex [28,[43][44][45][46][47][48][49][50][51][52][53], (ii) an in situ generated complex by addition of a metal salt and a ligand [54][55][56][57][58][59], or (iii) a metal organic framework (MOF) [60][61][62]. In some instances a base is used to facilitate the deprotonation of the nitroalkane [56,63,64].…”
Section: Introductionmentioning
confidence: 99%
“…The same reaction catalyzed by a Cu II –pyridine–2,3,5,6‐tetracarboxylate framework led to a yield of 78 % after 36 h (Table S6, entry 8) . However, a 2D Zn II framework of 4‐(pyridin‐4‐ylcarbamoyl)benzoate heterogeneously catalyzed the reaction with an overall yield of 93 % at 70 °C after 48 h (Table S6, entry 2), a yield that is identical to that of catalyst 1 (Table S6, entry 1).…”
Section: Catalytic Activitysupporting
confidence: 64%
“…[35] In comparison to the few examples found in the literature for the catalytic nitroaldol reaction in aqueous medium by using catalysts based on different transition metals (Table S1), the yields observed in this work are comparable or even better in some cases, taking into consideration the reaction conditions such as temperature, amount of catalyst, and reaction time. [35,36,[67][68][69][70][71][72] Aerobic oxidation of benzyl alcohol…”
Section: Nitroaldol (Henry) Reactionmentioning
confidence: 99%